Near-infrared 3D printing hydrogel and preparation method thereof
Through near-infrared 3D printing hydrogel technology, the acid-modified upconverted nanoparticles are used to stimulate acid-modified upconverted nanoparticles to generate ultraviolet light, solving the problems of high energy consumption and uneven curing of traditional ultraviolet light curing, and achieving the effects of low energy consumption, fast curing and uniform curing.
Patent Information
- Application Number
- CN202411830923.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
In the existing 3D printing technology, the energy consumption is high during ultraviolet curing, and the degree of curing in local areas is different or the curing time is long, which affects the uniformity and performance of the material.
Using near-infrared 3D printed hydrogel, it is cured by 3D printing and near-infrared light irradiation by bioink, and uses acid-modified upconversion nanoparticles and photoinitiators to generate ultraviolet light under near-infrared light excitation, promoting material curing.
It reduces energy consumption, shortens curing time, improves curing depth and uniformity, and solves the problems of high energy consumption and local uneven curing of traditional ultraviolet curing.
Smart Images

Figure CN119613624A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing, and in particular relates to a near-infrared 3D printing hydrogel and a preparation method thereof. Background Art
[0002] 3D printing, as an additive manufacturing technology, has experienced rapid development and widespread application since it was first introduced in the 1980s. Traditional 3D printing has high design freedom, allowing designers to achieve complex geometric shapes during the design process; high material utilization efficiency, adding materials only where needed, thereby reducing waste; physical models can be produced in a short time, greatly shortening the product development cycle; and can be customized according to user needs.
[0003] The main working principle of 3D printing is to use ultraviolet light to cure photosensitive resin, which can achieve high resolution and fine details. However, since the energy distribution of the ultraviolet light source may be uneven, for thicker parts, although the surface layer can be cured well, the internal layer may not be fully cured, and the curing time is usually long, which affects the uniformity and performance of the material. In addition, ultraviolet light curing requires a high-intensity ultraviolet light source to ensure rapid and complete curing of the resin. This may lead to increased energy consumption of the equipment and high requirements for cooling and maintenance of the ultraviolet light source. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a near-infrared 3D printing hydrogel and a preparation method thereof, and solve the technical problems in the prior art of 3D printing using ultraviolet light curing, such as high energy consumption and different curing degrees in local areas or long curing time.
[0005] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a near-infrared 3D printing hydrogel, which is prepared by curing biological ink by 3D printing and near-infrared light irradiation; wherein, by weight, the raw materials of the biological ink include 0.2-0.8 parts of acid-modified upconversion nanoparticles, 0.05-0.2 parts of photoinitiator, 1.5-2.5 parts of organic solvent, 1.0-2.0 parts of acrylic acid, 0.02-0.04 parts of cellulose, and 1.2-1.8 parts of deionized water; the upconversion nanoparticles are core-shell materials with doped NaYF4 as the core and NaYF4 as the shell; the doping elements in the doped NaYF4 include Yb 3+ and Tm 3+ .
[0006] In a second aspect, the present invention provides a method for preparing a near-infrared 3D printing hydrogel, comprising the following steps: dissolving cellulose in deionized water to obtain a solution A; mixing a photoinitiator and an organic solvent evenly to obtain a photoinitiator solution, and then adding acrylic acid to obtain a solution B; mixing solution A and solution B evenly under light-proof conditions, and then adding acid-modified upconversion nanoparticles and mixing evenly to obtain a biological ink; and curing the biological ink through 3D printing and near-infrared light irradiation to form a near-infrared 3D printing hydrogel.
[0007] Compared with the prior art, the beneficial effects of the present invention include: The present invention uses near-infrared light as a printing light source to effectively enhance the curing depth during the curing process of the material, and encapsulates an acid-modified upconversion nanoparticle material that emits ultraviolet light and a photoinitiator that absorbs ultraviolet light in a bio-ink as a printing slurry. Under the excitation of near-infrared light, Yb in the acid-modified upconversion nanoparticle material is converted into 3+ As a sensitizer, Tm absorbs laser light. 3+ As an activator, ultraviolet light of different wavelengths such as 291nm and 358nm is emitted. The initial curing of the liquid ink is achieved by matching the absorption spectrum of the photoinitiator with the emission spectrum of the acid-modified up-conversion nanoparticles, and the active oxygen generated in the NVP is used to promote the hydrogen bonding between acrylic acid and other materials in the bio-ink, and further achieve the curing of a hydrogel of a specific shape. The 291nm ultraviolet light belongs to the deep ultraviolet region, has higher energy, and is more conducive to promoting curing, thereby shortening the curing time and deepening the curing depth. Therefore, the bio-ink of the present invention itself can achieve the conversion from near-infrared light to ultraviolet light, and release active oxygen and heat energy, thereby achieving directional curing of the fluid bio-ink, and obtaining a near-infrared 3D printed hydrogel. The preparation method of the present invention has low energy consumption, short curing time and uniform curing degree. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 The highly efficient upconversion nanoparticles NaYF4:Yb 3+ ,Tm 3+ @Flowchart of the preparation method of NaYF4 nanomaterials; Figure 2 The NaYF4:39%Yb,1%Tm micron particles prepared in Comparative Example 1 of the present invention and the acid-modified NaYF4:Yb prepared in Example 1 are 3+ ,Tm 3+ @XRD diagram of NaYF4 high-efficiency upconversion nanoparticles compared with standard cards; Figure 3 The acid-modified NaYF4:Yb prepared in Example 1 of the present invention 3+ ,Tm 3+ @NaYF4 nanoparticles and NaYF4 prepared in Comparative Example 1: 39% Yb3+ ,1%Tm 3+ Upconversion luminescence spectrum of micron particles; Figure 4 The acid-modified NaYF4:Yb prepared by the present invention 3+ ,Tm 3+ @Emission spectrum of NaYF4 nanoparticles and absorption spectrum of photoinitiator TPO; Figure 5 It is a diagram of a near-infrared 3D printing hydrogel device and a printed sample of the present invention; Figure 6 This is a graph of the maximum stretching distance of the near-infrared 3D printed hydrogel of the present invention at different CMC contents, and the original length of the sample is 1 cm; Figure 7 This is a test diagram of the tensile and adhesive properties of the near-infrared 3D printed hydrogel prepared by the present invention; Figure 8 This is a depth test diagram of the near-infrared 3D printing hydrogel prepared by the present invention and ordinary UV curing. DETAILED DESCRIPTION
[0009] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0010] In view of the shortcomings of the prior art, the present invention provides a near-infrared 3D printing hydrogel and its preparation method and application, which can use a near-infrared light source to cure a specific hydrogel material. Compared with ultraviolet light curing, the energy output of the near-infrared light source is usually low, but it can effectively stimulate the curing reaction of the material and reduce energy consumption. At the same time, by optimizing the curing process, better interlayer bonding can be achieved, and the overall strength and toughness of the printed part can be improved. And by using polymers sensitive to near-infrared light, these materials can achieve efficient curing without the need for complex formulas. The present invention utilizes the ultraviolet luminescence of 980nm light-excited acid-modified upconversion nanoparticles, a part of which is directly applied to the photocuring of the hydrogel, and the remaining luminescence is absorbed by the photoinitiator TPO to promote the release of active oxygen by NVP, thereby promoting AA to connect with hydrogen bonds in the mixed solution to achieve hydrogel curing, which not only solves the need to control energy consumption in traditional ultraviolet light curing, and the serious problem of different degrees of curing in local areas, but also greatly improves the curing depth in the material curing process.
[0011] The up-conversion nanoparticles used in the present invention are core-shell materials with NaYF4 as the core and NaYF4 as the shell; the doping elements in the doped NaYF4 include Yb 3+ and Tm 3+For ease of description, the upconversion nanoparticles are denoted as NaYF4:Yb 3+ ,Tm 3 + @NaYF4.
[0012] In a first aspect, the present invention provides a near-infrared 3D printing hydrogel, which is prepared by 3D printing of biological ink and curing by near-infrared light irradiation, wherein the raw materials of the biological ink include acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 0.2-0.8 parts, photoinitiator 0.05-0.2 parts, organic solvent 1.5-2.5 parts, acrylic acid 1.0-2.0 parts, cellulose 0.02-0.04 parts, deionized water 1.2-1.8 parts.
[0013] Preferably, acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 preparation method, see Figure 1 , the specific steps include: (1) Using YCl3 aqueous solution, YbCl3 aqueous solution and TmCl3 aqueous solution as raw materials, doped NaYF4 was prepared by thermal cracking method, which was recorded as NaYF4:Yb,Tm; the molar ratio of YCl3, YbCl3 and TmCl3 was (0.5-0.6): (0.39-0.43): (0.01-0.07); (2) NaYF4:Yb,Tm was mixed with a mixed liquid of yttrium chloride-oleic acid precursor and sodium trifluoroacetate-oleic acid precursor, and NaYF4:Yb was synthesized by hot injection method. 3+ ,Tm 3+ @NaYF4; The molar ratio of NaYF4:Yb,Tm and yttrium in the mixed liquid is (0.125~0.15):(0.06~0.1); (3) Using acid to treat NaYF4:Yb 3+ ,Tm 3+ @NaYF4 was treated to remove the oleic acid ligand from the surface to obtain acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4.
[0014] Preferably, in step (1), the thermal cracking method specifically comprises: mixing YCl3 aqueous solution, YbCl3 aqueous solution and TmCl3 aqueous solution with octadecene and oleic acid, and keeping the mixture at 90-100°C for 5-15 min under a protective atmosphere, heating the mixture to 105-115°C for 0.8-1.2 h, heating the mixture to 120-140°C for 12-18 min to remove the remaining small amount of water, heating the mixture to 145-155°C for 20-40 min, and then cooling the mixture to 40-45°C; adding NaOH methanol solution and NH4F methanol solution to the above reaction solution, heating the mixture to 46-55°C for 20-40 min, and then heating the mixture to 290-305°C for 50-70 min, cooling the mixture to room temperature, and washing the mixture to obtain doped NaYF4.
[0015] Further preferably, in the thermal cracking method, the molar ratio of YCl3, YbCl3 and TmCl3 is (0.5-0.6): (0.39-0.43): (0.01-0.07); the volume ratio of YCl3 aqueous solution, octadecene and oleic acid is (0.5-0.6): (12-15): (5-8); the volume ratio of YCl3 aqueous solution, NaOH methanol solution and NH4F methanol solution is (0.5-0.6): (1.5-2.5): (6-7); the concentration of NaOH methanol solution is 0.8-1.2 mmol / mL, and the concentration of NH4F methanol solution is 0.4-0.6 mmol / mL.
[0016] Preferably, in step (2), the hot injection method specifically comprises: mixing the doped NaYF4 cyclohexane dispersion, octadecene and oleic acid, first heating to remove the cyclohexane under a protective atmosphere, then heating to 260-280°C under condensation reflux, injecting a mixed liquid of yttrium chloride-oleic acid precursor and sodium trifluoroacetate-oleic acid precursor three times within 3 hours, and finally cooling to room temperature, washing and drying to obtain upconversion nanoparticles.
[0017] Further preferably, in the hot injection method, the volume ratio of the doped NaYF4 cyclohexane dispersion, octadecene and oleic acid is (2-3):6:4; the concentration of the NaYF4 cyclohexane dispersion is 0.04-0.08 mmol / mL; the volume ratio of the doped NaYF4 cyclohexane dispersion, yttrium chloride-oleic acid precursor and sodium trifluoroacetate-oleic acid precursor is (2-3):(3.5-4.5):(1.5-2.5); the concentration of yttrium element in the yttrium chloride-oleic acid precursor is 0.01-0.03 mmol / mL, and the concentration of fluorine element in the sodium trifluoroacetate-oleic acid precursor is 1.1-1.3 mmol / mL.
[0018] Further preferably, the preparation method of the yttrium chloride-oleic acid precursor comprises the following steps: mixing 5 ml of 0.1 M yttrium chloride solution with 15 ml of octadecene and 10 ml of oleic acid, stirring and heating to 100 ° C in a protective gas for 10 min, heating to 110 ° C for 1 h, continuing to heat to 130 ° C for 15 min, then continuing to heat to 150 ° C for 30 min, and finally cooling to room temperature, putting it into a glass bottle and storing it in a refrigerator.
[0019] Further preferably, the preparation method of sodium trifluoroacetate-oleic acid precursor comprises the following steps: taking 4.486 grams of sodium trifluoroacetate powder and dissolving it in 2 ml of methanol by ultrasonication, then adding 80 ml of oleic acid and placing it in a vacuum environment to allow the methanol solution to completely evaporate, and finally sealing it and storing it in a refrigerator.
[0020] The present invention obtains acid-modified NaYF4:Yb by changing the type and ratio of doping elements and adding an acid modification treatment step. 3+ ,Tm 3+ @NaYF4; Through the acid modification treatment step, the surface oleic acid ligands of the nanoparticles are removed, making them soluble in water and convenient for the preparation of bio-ink.
[0021] Preferably, in step (1), the concentrations of the YCl3 aqueous solution, the YbCl3 aqueous solution and the TmCl3 aqueous solution are all 1 mmol / mL.
[0022] Preferably, in step (1), the molar ratio of YCl3, YbCl3 and TmCl3 is 0.6:0.39:0.01; NaYF4:Yb,Tm is NaYF4:39%Yb,1%Tm. The doping ratio of elements affects the luminescence performance, specifically affects the energy transfer between Yb and Tm, and further affects the luminescence spectrum. The present invention controls the doping ratio of Yb and Tm and forms a core-shell structure with NaYF4 to better regulate the acid-modified NaYF4:Yb 3+ ,Tm 3+ Ultraviolet luminescence of @NaYF4 material.
[0023] Preferably, in step (3), the modification treatment specifically comprises: dispersing NaYF4:Yb,Tm@NaYF4 in cyclohexane to obtain a first dispersion, adding hydrochloric acid to the first dispersion, mixing and centrifuging; after the centrifugation, pouring off the supernatant, adding water and ethanol to the remaining material to obtain a second dispersion; removing the liquid in the second dispersion and drying to obtain acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4.
[0024] Further preferably, the concentration of the first dispersion is 8-12 mg / mL; the concentration of hydrochloric acid is 0.05-0.15 mol / L, the volume ratio of the first dispersion and hydrochloric acid is (3-5):1; the ratio between NaYF4:Yb,Tm@NaYF4, water and ethanol is 40 mg:(2-4) mL:(3-5) mL.
[0025] Preferably, the photoinitiator comprises diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO).
[0026] Preferably, the organic solvent comprises N-vinyl pyrrolidone (NVP).
[0027] Preferably, the cellulose comprises CMC.
[0028] In a second aspect, the present invention provides a method for preparing a near-infrared 3D printing hydrogel, comprising the following steps: Dissolve cellulose in deionized water to obtain solution A; The photoinitiator and the organic solvent are uniformly mixed to obtain a photoinitiator solution, and acrylic acid is added to obtain a solution B; Under light-proof conditions, mix solution A and solution B evenly, then add acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 were mixed evenly to obtain bio-ink; The bio-ink is cured through 3D printing and near-infrared light irradiation to form near-infrared 3D printed hydrogel.
[0029] Preferably, since the actual amount of CMC used is relatively small, a certain amount of solution is prepared first and then taken out. Specifically, CMC is added into deionized water and fully stirred and dissolved as solution A, with a mass concentration of 2 to 7.5%.
[0030] Preferably, the near infrared light adopts 980nm laser.
[0031] The present invention also provides a near-infrared 3D printing hydrogel device, which can use a commercially available 3D printer; it can also use a commercially available laser to improve the hot melt adhesive curing printing device, specifically, the device for placing the slurry on the original hot melt adhesive curing printing device is removed, and the laser is fixed in the printing device, and the movement path of the laser is controlled by the movement of the coordinate axis in the 3D space, and it is ensured that the directional movement of the laser can be accurately driven during the movement of the coordinate axis inside the printing device. In order to prevent excessive penetration of the laser, a circular opaque ceramic sheet needs to be placed at the bottom of the printing device, so that the bio-ink can be equipped in the printing device.
[0032] The maximum power of the laser is 3w / cm 3 Zoomable 980nm laser.
[0033] The near-infrared 3D printing hydrogel printing process is as follows: the laser is used as a light source to emit 980nm laser to the bio-ink printed by the 3D printer. The bio-ink absorbs the 980nm laser to generate ultraviolet light of different wavelengths such as 291nm and 358nm. According to the absorption spectrum of TPO and acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 emission spectrum is matched to achieve preliminary solidification of liquid ink; in addition, the active oxygen generated in NVP is used to promote hydrogen bonding between AA and other materials in the bio-ink to further achieve the solidification of hydrogels of specific shapes.
[0034] The biological ink of the present invention is stored in a brown light-proof bottle at room temperature and is taken out to a glass culture dish for printing and curing during printing.
[0035] The main mechanism of action and advantages of the present invention are: (1) The acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 material is a core-shell structure. The coating of the core-shell structure can passivate the amorphous area on the surface of the original particles, thereby enhancing the optical properties of the upconversion nanoparticles; (2) The main function of NVP in the present invention is to dissolve the photoinitiator; then more acrylic acid is added to form a hydrogel through the hydrogen bonding between acrylic acid (AA) and cellulose (CMC); CMC itself is brittle and hard. If the CMC content is too high, it is easy to produce adverse effects. Therefore, the CMC content in the present invention is controlled to be relatively small to obtain a hydrogel with good flexibility.
[0036] The present invention is further described in detail below through specific examples and comparative examples.
[0037] Example 1 The acid-modified NaYF4:Yb 3+ ,Tm 3+ The preparation method of @NaYF4 comprises the following steps: (1) 0.6 mL of 1 mmol / ml YCl3 aqueous solution, 0.39 mL of 1 mmol / ml YbCl3 aqueous solution, and 0.01 mL of 1 mmol / ml TmCl3 aqueous solution were mixed in 14 mL of octadecene (ODE) and 6 mL of oleic acid (OA), so that the amount of YCl3, YbCl3, and TmCl3 was 0.6:0.39:0.01. First, in a high-purity argon atmosphere, the mixture was heated to 100°C with stirring at a speed of 600 rad / min and kept warm for 10 min, then heated to 110°C and kept warm for 1 h to remove excess water, then heated to 130°C and kept warm for 15 min to remove the remaining small amount of water, then heated to 150°C and kept warm for 30 min to dissolve the drug wrapped by oleic acid, and then cooled to 45°C. Then, add 2mL of 1mmol / ml NaOH methanol solution and 6.6mL of 0.5mmol / ml NH4F methanol solution to the above reaction solution; raise the temperature to 49℃ and keep it for 30min, then continue to raise the temperature to 304℃ and keep it for 60min for nucleation and crystallization, then cool the solution to room temperature, and the sample preparation is complete. Finally, wash the reaction sample with anhydrous ethanol / cyclohexane to obtain NaYF4:39%Yb,1%Tm nanocrystals; disperse the prepared NaYF4:39%Yb,1%Tm nanocrystals in 10mL cyclohexane for later use; (2) Take 2.5mL of the above NaYF4:39%Yb,1%Tm liquid (Y molar amount is 0.15mmol), 6mL of octadecene and 4mL of oleic acid and add them into a three-necked flask, stir at a speed of 800rad / min in a high-purity argon atmosphere and slowly heat to 100℃ for 30min to remove cyclohexane. Secondly, heat to 270℃ under condensation reflux, and slowly inject 4mL of yttrium chloride-oleic acid precursor (Y molar amount is 0.08mmol) and 2mL of sodium trifluoroacetate-oleic acid precursor (F molar amount is 2.4mmol) into the mixed liquid three times within 3h. Finally, after the core-shell structure growth is completed, cool down to room temperature, take out the sample, wash it with anhydrous ethanol / cyclohexane, and dry it into powder to obtain NaYF4:Yb,Tm@NaYF4 material; (3) Disperse 40 mg NaYF4:Yb,Tm@NaYF4 in 4 mL cyclohexane and add to a centrifuge tube. Then add 1 mL 0.1 M dilute hydrochloric acid and mix well. Centrifuge at 1000 rad for 5 min and pour off the supernatant. Add 3 mL water to dissolve and disperse. Add 4 mL ethanol to wash and pour off the liquid. Dry the remaining material at 60 ° C to obtain a powder for later use. The acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4.
[0038] A method for preparing a near-infrared 3D printing hydrogel comprises the following steps: (1) Add 2 g of CMC into 98 mL of deionized water and stir thoroughly to dissolve as solution A. The mass concentration of solution A is 2%; 0.1 g of TPO particles were dissolved in 2.1 g of NVP to obtain a photoinitiator solution, and 1.4 g of AA was added to the photoinitiator solution to form 3.6 g of solution B; (2) At room temperature and in the dark, mix 1.5 g of solution A (i.e., the actual amount of CMC used is 0.03 g, and the actual amount of water used is 1.47 g) with 3.6 g of solution B and stir them evenly, and add 0.57 g of acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 particles, mixed evenly with bio-ink, it was calculated that the proportion of CMC in the bio-ink was 0.5%; (3) The bio-ink is cured by 3D printing and irradiation with 980nm near-infrared light to form a near-infrared 3D printed hydrogel.
[0039] Example 2 The only difference from Example 1 is that the mass concentration of solution A in step (1) is adjusted. After taking 1.5 g of solution A, the proportion of CMC in the obtained bio-ink is 0.3%, 0.4%, 0.6% and 0.7%, respectively. The other steps and conditions are the same as in Example 1.
[0040] Example 3 The only difference from Example 1 is that the acid-modified NaYF4:Yb 3+ ,Tm 3+ The dosage of @NaYF4 is shown in Table 1 below, and the other steps and conditions are the same as those in Example 1.
[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that the acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 uses NaYF4: 39% Yb, 1% Tm micron crystals, and the other steps and conditions are the same as those in Example 1; the specific preparation steps of NaYF4: 39% Yb, 1% Tm micron crystals are as follows: Take 0.3332g of NaF powder, 0.70039g of YF3 powder, 0.61476g of Yb2O3 powder, and 0.018076g of TmF3 powder and add them into a ceramic mortar. Add anhydrous ethanol and grind and mix them evenly. After the powder is ground and dried, it is calcined and crystallized at 700℃ in a high-temperature furnace. After crystallization, take out the sample, grind it several times, and put it into a sample bag for storage.
[0042] Comparative Example 2 The difference between this comparative example and Example 1 is that the acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 uses NaYF4: 39% Yb, 1% Tm nanocrystals prepared in Example 1, and the other steps and conditions are the same as in Example 1.
[0043] Performance Testing The acid-modified NaYF4:Yb prepared in Example 1 above 3+ ,Tm 3+ The XRD patterns (X-ray diffraction patterns) of NaYF4:39%Yb,1%Tm (i.e., NaYF4:Yb,Tm in the figure) prepared in @NaYF4 and Comparative Example 1 are compared with those of the standard card. Figure 2 As shown; Figure 2 It shows that since the diffraction peaks of the prepared samples match the standard PDF card 16-0334, it shows that the synthesized nanoparticles are pure phase and the required nanoparticles have been successfully prepared.
[0044] Acid-modified NaYF4:Yb prepared in Example 1 of the present invention 3+ ,Tm 3+ @NaYF4 is a nanoparticle with a uniform particle size distribution, and the average particle size is about 35nm, and it also has good crystallinity.
[0045] Depend on Figure 3 It can be seen that under the irradiation of 980nm laser, the acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF4 material can effectively emit the blue-violet light required in the cross-linking process of hydrogel, especially the obvious ultraviolet light at around 291nm, which belongs to the UVB band in the deep ultraviolet region (280-320nm) and has higher energy. Combined with ultraviolet light of different wavelengths such as 358nm, it is more conducive to promoting curing, thereby shortening the curing time and deepening the curing depth. 3+ ,1%Tm 3+ The micron particles of comparative example 1 emit light mainly at around 480nm and 700nm, and the nanoparticles of comparative example 2 emit light at a reduced level, but weak ultraviolet light appears at 360nm, but there is no light emission at 291nm in comparative example 1 and comparative example 2; thus, it is shown that the present invention produces a synergistic effect by regulating the doping ratio of NaYF4:Yb,Tm elements, controlling the particle size at the nanometer level through the preparation process, and compounding NaYF4 to form a core-shell structure, thereby promoting the acid-modified NaYF4:Yb 3+ ,Tm 3+ Ultraviolet luminescence of @NaYF4 material.
[0046] Depend on Figure 4 It can be seen that the data show that the absorption spectrum of the photoinitiator overlaps with the up-conversion emission spectrum with blue-violet light emission, which indicates that the ink prepared with the particles has the possibility of preparing hydrogels.
[0047] The near-infrared 3D printing hydrogel prepared in the above examples and comparative examples was used as bio-ink, and a 980nm laser was used to emit laser light to the bio-ink. The bio-ink achieved the conversion from near-infrared light to ultraviolet light, and released active oxygen and heat energy, thereby achieving directional curing of the fluid bio-ink. The specific curing results are shown in FIG. Figure 5 shown.
[0048] Depend on Figure 5 It can be seen that the near-infrared 3D printing hydrogel device of the present invention is to remove the device for placing the slurry on the original hot melt adhesive curing printing device, and fix the laser in the printing device, and use the movement of the coordinate axis in the 3D space to control the movement path of the laser, and ensure that the directional movement of the laser can be accurately driven during the movement of the coordinate axis inside the printing device. In order to prevent excessive penetration of the laser, a circular opaque ceramic sheet is also placed at the bottom of the printing device, so that the bio-ink can be equipped in the printing device. Combined with the bio-ink prepared in Example 1, it can be successfully printed and a uniform molded sample can be obtained.
[0049] The near-infrared 3D printed hydrogels obtained in the examples and comparative examples were tested as samples for bio-ink printing. The results are as follows: Figure 6 , Figure 7 And as shown in Table 1.
[0050] Depend on Figure 6 It can be seen that the original length of the hydrogel prepared in Example 2 before stretching is 1 cm. After stretching, as the CMC content increases, the tensile performance first increases and then decreases. The elongation reaches the maximum value at 0.5%, indicating that the performance is best when the CMC content in the printing ink is 0.5%. The specific performance test results are shown in Table 1 below.
[0051] Table 1 Tensile properties of bio-inks with different CMC concentrations in Example 2
[0052] At the same time by Figure 7 It can be seen that the hydrogel prepared in Example 1 of the present invention has good tensile properties and skin adhesion, can be bent at multiple angles, and can be applied to the fields of skin wound healing and skin wound sterilization.
[0053] Table 2 shows the acid-modified NaYF4:Yb used in the bio-ink for near-infrared 3D printing of hydrogel in Example 3 of the present invention. 3 + ,Tm 3+@The effect of different amounts of NaYF4 on the curing time of hydrogel.
[0054] Table 2 Curing speed of biological inks with different ratios in Example 3
[0055] As shown in Table 2, during the printing process, as the acid-modified NaYF4:Yb 3+ ,Tm 3+ @As the concentration of NaYF4 in the bio-ink increases, its curing effect also improves. When its concentration reaches 10%, the solubility of the particles in the solution gradually reaches saturation. Under the same conditions, the emission spectrum of Comparative Example 1 is more concentrated around 475nm, lacks 291nm emission, and the particles are too large to make it soluble in the solution, resulting in poor curing. Comparative Example 2 has a lower luminous intensity than Example 1, resulting in a poor curing effect. Therefore, the raw materials of the bio-ink of the present invention preferably include acid-modified NaYF4:Yb 3+ ,Tm 3+ @NaYF40.2~0.8 parts, further 0.2~0.6 parts.
[0056] Figure 8 The curing effect of the bio-ink prepared in Example 1 is demonstrated, and the external excitation light sources used are different. When the 365nm ultraviolet lamp is used to directly cure the bio-ink, it can be found that only the liquid on the surface is cured, while the deeper liquid is not cured due to the poor penetration of ultraviolet light. The 980nm near-infrared laser has higher penetration and is more likely to achieve the effect of curing the liquid from the inside to the outside.
[0057] In summary, the present invention uses improved bio-ink to prepare near-infrared 3D printing hydrogel under 980nm laser; wherein the improved bio-ink includes NaYF4:Yb 3+ ,Tm 3+@NaYF4 (UCNP), diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO), acrylic acid (AA), N-vinyl pyrrolidone (NVP), cellulose (CMC) material mixed liquid. The laser is fixed and the bio-ink is placed by the printing device. The laser emits a light source to the bio-ink, and the printing device can control the movement trajectory of the laser in a directional manner to irradiate the UCNP in the bio-ink to emit blue-violet light. On the one hand, the blue-violet light is absorbed by TPO to directly promote the photocuring of the hydrogel. On the other hand, the NVP is chemically promoted to produce active oxygen, thereby generating hydrogen bonds between AA and CMC to achieve customized 3D printing of hydrogel. The present invention puts the bio-ink in a glass culture dish as a curing device for near-infrared 3D printing, which not only uses the characteristics of the material in the bio-ink to realize customized 3D printing of hydrogels, but also uses the high penetration of the 980nm laser to achieve the curing of hydrogel products with higher penetration depth. Therefore, the present invention has good detection accuracy and real-time response characteristics, can accurately identify the measurement target, and realize high-precision, controllable shape dynamic near-infrared 3D printing.
[0058] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A near-infrared 3D printing hydrogel, characterized in that: It is made by 3D printing of bio-ink and curing with near-infrared light; Wherein, the raw materials of the bio-ink include, by weight, 0.2 to 0.8 parts of acid-modified upconversion nanoparticles, 0.05 to 0.2 parts of photoinitiator, 1.5 to 2.5 parts of organic solvent, 1.0 to 2.0 parts of acrylic acid, 0.02 to 0.04 parts of cellulose, and 1.2 to 1.8 parts of deionized water; The up-conversion nanoparticles are core-shell materials with doped NaYF4 as the core and NaYF4 as the shell; the doping elements in the doped NaYF4 include Yb 3+ and Tm 3+ .
2. The near-infrared 3D printing hydrogel according to claim 1, characterized in that: The method for preparing acid-modified upconversion nanoparticles comprises the following specific steps: (1) Using YCl3 aqueous solution, YbCl3 aqueous solution and TmCl3 aqueous solution as raw materials, doped NaYF4 was prepared by thermal cracking; the molar ratio of YCl3, YbCl3 and TmCl3 was (0.5-0.6): (0.39-0.43): (0.01-0.07); (2) mixing the doped NaYF4 with a mixed liquid of a yttrium chloride-oleic acid precursor and a sodium trifluoroacetate-oleic acid precursor, and synthesizing upconversion nanoparticles by a hot injection method; the molar ratio of the doped NaYF4 and the yttrium element in the mixed liquid is (0.125-0.15): (0.06-0.1); (3) The upconversion nanoparticles are modified by removing oleic acid ligands from their surfaces using an acid solution to obtain acid-modified upconversion nanoparticles.
3. The near-infrared 3D printing hydrogel according to claim 2, characterized in that: In step (1), the thermal cracking method specifically includes: mixing YCl3 aqueous solution, YbCl3 aqueous solution and TmCl3 aqueous solution with octadecene and oleic acid, keeping the mixture at 90-140°C to remove moisture under a protective atmosphere, heating the mixture to 145-155°C and keeping the mixture for 20-40 min, and then cooling the mixture to 40-45°C; adding NaOH methanol solution and NH4F methanol solution to the above reaction solution, heating the mixture to 46-55°C and keeping the mixture for 20-40 min, and then heating the mixture to 290-305°C and keeping the mixture for 50-70 min, cooling the mixture to room temperature and washing the mixture to obtain doped NaYF4.
4. The near-infrared 3D printing hydrogel according to claim 2, characterized in that: In step (2), the hot injection method specifically includes: mixing the doped NaYF4 cyclohexane dispersion, octadecene and oleic acid, first heating to remove cyclohexane under a protective atmosphere, then heating to 260-280°C under condensation reflux, injecting a mixed liquid of yttrium chloride-oleic acid precursor and sodium trifluoroacetate-oleic acid precursor three times within 3 hours, and finally cooling to room temperature, washing and drying to obtain upconversion nanoparticles.
5. The near-infrared 3D printing hydrogel according to claim 2, characterized in that: In step (3), the modification treatment specifically includes: Dispersing the upconversion nanoparticles in cyclohexane to obtain a first dispersion, adding hydrochloric acid to the first dispersion, mixing well, and then centrifuging; After centrifugation, the supernatant was poured off, and water and ethanol were added to the remaining material to obtain a second dispersion; The liquid in the second dispersion is removed and then dried to obtain acid-modified up-conversion nanoparticles.
6. The near-infrared 3D printing hydrogel according to claim 5, characterized in that: The concentration of the first dispersion is 8 to 12 mg / mL; The concentration of the hydrochloric acid is 0.05-0.15 mol / L, and the volume ratio of the first dispersion to the hydrochloric acid is (3-5):1; The ratio of the upconversion nanoparticles, water and ethanol is 40 mg: (2-4) mL: (3-5) mL.
7. The near-infrared 3D printing hydrogel according to claim 1, characterized in that: The photoinitiator includes diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide; The organic solvent includes N-vinyl pyrrolidone; The cellulose includes CMC.
8. The near-infrared 3D printing hydrogel according to claim 1, characterized in that: Under near-infrared light excitation, the acid-modified up-conversion nanoparticles emit ultraviolet light, and the wavelength of the ultraviolet light includes 291nm and 358nm.
9. The method for preparing a near-infrared 3D printing hydrogel according to any one of claims 1 to 8, characterized in that: The following steps are involved: Dissolve cellulose in deionized water to obtain solution A; The photoinitiator and the organic solvent are uniformly mixed to obtain a photoinitiator solution, and acrylic acid is added to obtain a solution B; Under light-proof conditions, solution A and solution B are mixed evenly, and then acid-modified upconversion nanoparticles are added and mixed evenly to obtain bio-ink; The bio-ink is cured through 3D printing and near-infrared light irradiation to form near-infrared 3D printed hydrogel.
10. The method for preparing near-infrared 3D printing hydrogel according to claim 9, characterized in that: The near infrared light uses 980nm laser.